Evaluation Study of Short-Term Programs at a Residential School for Students who are Blind and Visually Impaired. (January 2013) - Pogrund, Rona L.; Darst, Shannon; Boland, Teryl
Introduction: The results of a 2009–2010 program evaluation study that examined parents, teachers of students with visual impairments, administrators, and students regarding overall satisfaction with and effectiveness of the short-term programs at a residential school for students who are blind and visually impaired are described. The findings are presented with recommendations for program improvement. Methods: The mixed-method triangulation study design included the collection of multiple phases of quantitative and qualitative data. The setting was the short-term programs at a special purpose or residential school for students who are blind. All participants had at least one experience with short-term programs. Participants were chosen by convenience sampling and included 107 parents, 87 teachers of students with visual impairments, 26 administrators, and six students. Of these participants, the initial overall response rates were 21 of 107 parents (19.62%), 54 of 87 teachers of students with visual impairments (62.07%), 8 of 39 administrators (20.5%), and 6 of 6 students (100%). Results: Fifteen (71.4%) parents, forty-seven (82.5%) teachers of students with visual impairments, and eight (100%) administrators felt that short-term programs are an effective tool in meeting the specific needs of students with visual impairments. Twenty-one (65.6%) parents, fifty-two (60.4%) teachers of students with visual impairments, and five (62.5%) administrator respondents stated that their overall satisfaction with short-term programs was outstanding. All six students felt that short-term programs were beneficial to them. All percentages were calculated with confidence intervals of 95%. Discussion: The findings demonstrate that the majority of participants felt that short-term programs are effective and more than satisfactory in meeting students' needs. Implications for practitioners: Other residential schools for students who are blind could model their short-term programs after the program in this study.